Hydrocarbon chain-length dependence of solvation dynamics in alcohol-based deep eutectic solvents: a two-dimensional infrared spectroscopic investigation - Chatterjee, Srijan; Ghosh, Deborin; Haldar, Tapas; Deb, Pranab; Sakpal, Sushil S.; Deshmukh, Samadhan H.; Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemistry B, 2019)
Deep eutectic solvents (DESs) have gained popularity in recent years as an environmentally benign, inexpensive alternative to organic solvents for diverse applications in chemistry and biology. Among them, alcohol-based DESs serve as useful media in various applications due to their significantly low viscosity as compared to other DESs. Despite their importance as media, little is known how their solvation dynamics change as a function of the hydrocarbon chain length of the alcohol constituent. In order to obtain insights into the chain-length dependence of the solvation dynamics, we have performed two-dimensional infrared spectroscopy on three alcohol-based DESs by systematically varying the hydrocarbon chain length. The results reveal that the solvent dynamics slows down monotonically with an increase in the chain length. This increase in the dynamic timescales also shows a strong correlation with the concomitant increase in the viscosity of DESs. In addition, we have performed molecular dynamics simulations to compare with the experimental results, thereby testing the capacity of simulations to determine the amplitudes and timescales of the structural fluctuations on fast timescales under thermal equilibrium conditions.

Transition of a deep eutectic solution to aqueous solution: a dynamical perspective of the dissolved solute - Sakpal, Sushil S.; Deshmukh, Samadhan H.; Chatterjee, Srijan; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2021)
Disruption of the deep eutectic solvent (DES) nanostructure around the dissolved solute upon addition of water is investigated by polarization-selective two-dimensional infrared spectroscopy and molecular dynamics simulations. The heterogeneous DES nanostructure around the solute is partially retained up to 41 wt % of added water, although water molecules are gradually incorporated in the solute's solvation shell even at lower hydration levels. Beyond 41 wt %, the solute is observed to be preferentially solvated by water. This composition denotes the upper hydration limit of the deep eutectic solvent above which the solute senses an aqueous solvation environment. Interestingly, our results indicate that the transition from a deep eutectic solvation environment to an aqueous one around the dissolved solute can happen at a hydration level lower than that reported for the ``water in DES'' to ``DES in water'' transition.

Association-dissociation dynamics of ionic electrolytes in low dielectric medium - Ghosh, Deborin; Sakpal, Sushil S.; Chatterjee, Srijan; Deshmukh, Samadhan H.; Kwon, Hyejin; Kim, Yung Sam; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Ionic electrolytes are known to form various complexes which exist in dynamic equilibrium in a low dielectric medium. However, structural characterization of these complexes has always posed a great challenge to the scientific community. An additional challenge is the estimation of the dynamic association-dissociation time scales (lifetime of the complexes), which are key to the fundamental understanding of ion transport. In this work, we have used a combination of infrared absorption spectroscopy, two-dimensional infrared spectroscopy, molecular dynamics simulations, and density functional theory calculations to characterize the various ion complexes formed by the thiocyanate-based ionic electrolytes as a function of different cations in a low dielectric medium. Our results demonstrate that thiocyanate is an excellent vibrational reporter of the heterogeneous ion complexes undergoing association-dissociation dynamics. We find that the ionic electrolytes exist as contact ion pairs, dimers, and clusters in a low dielectric medium. The relative ratios of the various ion complexes are sensitive to the cations. In addition to the interactions between the thiocyanate anion and the countercation, the solute-solvent interactions drive the dynamic equilibrium. We have estimated the association-dissociation dynamics time scales from two-dimensional infrared spectroscopy. The exchange time scale involving the cluster is faster than that between a dimer and an ion pair. Moreover, we find that the dynamic equilibrium between the cluster and another ion complex is correlated to the solvent fluctuations.

Does viscosity drive the dynamics in an alcohol-based deep eutectic solvent? - Chatterjee, Srijan; Deshmukh, Samadhan H.; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Deep eutectic solvents, consisting of heterogeneous nano-domains of hydrogen-bonded networks, have evolved into a range of viscous fluids that find applications in several fields. As viscosity is known to influence the dynamics of other neoteric solvents like ionic liquids, understanding the effect of viscosity on deep eutectic solvents is crucial to realize their full potential. Herein, we combine polarization-selective pump-probe spectroscopy, two-dimensional infrared spectroscopy, and molecular dynamics simulations to elucidate the impact of viscosity on the dynamics of an alcohol-based deep eutectic solvent, ethaline. We compare the solvent fluctuation and solute reorientation time scales in ethaline with those in ethylene glycol, an ethaline constituent. Interestingly, we find that the solute's reorientation apparently scales the bulk viscosity of the solvent, but the same is not valid for the overall solvation dynamics. Using the variations in the estimated intercomponent hydrogen bond lifetimes, we show that a dissolved solute does not sense the bulk viscosity of the deep eutectic solvent; instead, it senses domain-specific local viscosity determined by the making and breaking of the hydrogen bond network. Our results indicate that understanding the domain-specific local environment experienced by the dissolved solute is of utmost importance in deep eutectic solvents.

Ligand dynamics time scales identify the surface-ligandinteractions in thiocyanate-capped cadmium sulfide nanocrystals - Deshmukh, Samadhan H.; Chatterjee, Srijan; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2022)
The nanocrystal surface, which acts as an interface between thesemiconductor lattice and the capping ligands, plays a significant role in theattractive photophysical properties of semiconductor nanocrystals for use in awide range of applications. Replacing the long-chain organic ligands with shortinorganic variants improves the conductivity and carrier mobility of nanocrystal-based devices. However, our current understanding of the interactions betweenthe inorganic ligands and the nanocrystals is obscure due to the lack ofexperiments to directly probe the inorganic ligands. Herein, using two-dimensional infrared spectroscopy, we show that the variations in the inorganicligand dynamics within the heterogeneous nanocrystal ensemble can identifythe diversities in the inorganic ligand-nanocrystal interactions. The liganddynamics time scale in SCN-capped CdS nanocrystals identifies three distinctligand populations and provides molecular insight into the nanocrystal surface.Our results demonstrate that the SCN-ligands engage in a dynamic equilibriumand stabilize the nanocrystals by neutralizing the surface charges through both direct binding and electrostatic interaction.

On-off infrared absorption of the S=O vibrational probe of dimethyl sulfoxide - Chakrabarty, Suranjana; Deshmukh, Samadhan H.; Barman, Anjan; Bagchi, Sayan; Ghosh, Anup (Journal of Physical Chemistry B, 2022)
Dimethyl sulfoxide (DMSO), a polar solvent molecule, is used in a wide range of therapeutic and such as dimerization and hydrogen bonding with water, are crucial to understanding the role of DMSO in applications. Herein, we study DMSO in various solvation environments to decipher the environment-dependent dimerization and hydrogen-bonding propensity. We use a combination of infrared spectroscopy, quantum mechanical calculations, and molecular dynamics simulations to reach our conclusions. Although DMSO can exist in a dynamic equilibrium between monomers and dimers, our results show that the relative intensity of the S=O stretch and the CH3 rocking modes is a spectroscopic indicator of the extent of DMSO dimerization in solution. The dimerization (self-association) is seen to be maximum in neat DMSO. When dissolved in different solvents, the dimerization propensity decreases with increasing solvent polarity. In the presence of a protic solvent, such as water, DMSO forms a hydrogen bond with the solvent molecules, thereby reducing the extent of dimerization. Further, we estimate the hydrogen-bond occupancy of DMSO. Our results show that DMSO predominantly exists as doubly hydrogen-bonded in water.

Solvation structure and dynamics of a small ion in an organic electrolyte - Kore, Shivshankar; Sahoo, Rudhi Ranjan; Santra, Binit; Sarkar, Archishman; Chowdhury, Tubai; Deshmukh, Samadhan H.; Hazarika, Sulagna; Chatterjee, Srijan; Bagchi, Sayan (Journal of Photochemistry and Photobiology A-Chemistry, 2023)
Organic carbonates are commonly used as electrolytes in commercial lithium-ion batteries. A detailed interpretation of the solvation structure and dynamics of the electrolyte around ions is necessary to understand the charge/discharge process in batteries. This work combines infrared absorption spectroscopy with quantum chemical calculations and molecular dynamics simulations to decipher the solvation structure of propylene carbonate, a cyclic carbonate, around the dissolved thiocyanate ion. Two dimensional infrared spectroscopy and polarization-selective pump probe spectroscopies have been utilized to extract the timescales of solvent fluctuation and the solute reorientational dynamics. The similarity in the slow timescales for the solute and the solvent dynamics signifies that similar processes control both dynamics.

Perturbation of fermi resonance on hydrogen-bonded > C=O: 2D IR studies of small ester probes - Sakpal, Sushil; Chakrabarty, Suranjana; Reddy, Kambham Devendra; Deshmukh, Samadhan H.; Biswas, Rajib; Bagchi, Sayan; Ghosh, Anup (Journal of Physical Chemistry B, 2024)
We utilized linear and 2D infrared spectroscopy to analyze the carbonyl stretching modes of small esters in different solvents. Particularly noteworthy were the distinct carbonyl spectral line shapes in aqueous solutions, prompting our investigation of the underlying factors responsible for these differences. Through our experimental and theoretical calculations, we identified the presence of the hydrogen-bond-induced Fermi resonance as the primary contributor to the varied line shapes of small esters in aqueous solutions. Furthermore, our findings revealed that the skeletal deformation mode plays a crucial role in the Fermi resonance for all small esters. Specifically, the first overtone band of the skeletal deformation mode intensifies when hydrogen bonds form with the carbonyl group of esters, whereas such coupling is rare in aprotic organic solvents. These spectral insights carry significant implications for the utilization of esters as infrared probes in both biological and chemical systems.

Probing surface interactions in CdSe quantum dots with thiocyanate ligands - Deshmukh, Samadhan H.; Yadav, Sushma; Chowdhury, Tubai; Pathania, Akhil; Sapra, Sameer; Bagchi, Sayan (NANOSCALE, 2024)
Keywords: COLLOIDAL NANOCRYSTALS; STRUCTURAL DYNAMICS; Thin-films

Viscosity effects on the dynamics of diols and diol-based deep eutectic solvents - Chatterjee, Srijan; Deshmukh, Samadhan H.; Chowdhury, Tubai; Bagchi, Sayan (Photochemistry and Photobiology, 2024)
Diols, characterized by the presence of two hydroxyl groups, form extended hydrogen-bonded networks. Increasing hydrocarbon chain length is known to elevate the viscosity of diols. Given the established influence of viscosity on solvent dynamics, it becomes imperative to comprehend the impact of viscosity on the fluctuation dynamics within diols and establish connections with hydrogen bond formation and breaking dynamics. In this study, we employ two-dimensional infrared spectroscopy to investigate the viscosity dependence of the structural evolution dynamics in three diols with varying chain lengths. Complementing our experimental approach, molecular dynamics simulations are conducted to extract hydrogen bond lifetimes. Our findings reveal a linear correlation between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. Notably, the selected diols exhibit the capability to form deep eutectic solvents upon mixing with choline chloride at specific molar ratios. In contrast to molecular solvents like diols, deep eutectic solvents are characterized by the formation of heterogeneous nanodomains, comprising various intercomponent hydrogen-bonded networks. Interestingly, our observations indicate that while the fluctuation dynamics decelerate with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is not linear, in contrast to the observed linearity in diols. This nuanced understanding contributes to the broader comprehension of the interplay between viscosity and dynamics in both molecular and deep eutectic solvents. We investigate the impact of viscosity on structural evolution dynamics in diols with varying chain lengths. Employing two-dimensional infrared spectroscopy and molecular dynamics simulations, we explore the relationship between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. We report a linear correlation in diols between viscosity, fluctuation timescales, and hydrogen bond lifetimes. Diols also form deep eutectic solvents, characterized by heterogeneous nanodomains. While fluctuation dynamics slow down with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is nonlinear, contrasting with diols' linearity. This understanding enhances comprehension of viscosity-dynamics interplay in molecular and deep eutectic solvents.image
Keywords: Dynamics; Hydrogen bond; solvent; spectroscopy; viscosity